Spektroskopija protonsko vzbujenih rentgenskih žarkov - PIXE - Naseska, Mimoza (Matrika, 2016)
This article intends to introduce a spectroscopic method named Proton induced X-ray emissions, which has been in bloom in the past decades because of the continued advances in X-ray detectors. It is a reliable and accurate method to quantify 2D elemental maps of samples ranging from biological tissues, minerals and historical artefacts. First, we present the theoretical background needed to understand the method, then we present the experimental setup at the Tandetron accelerator that is a part of the Microanalytical centre which is a part of the F2 section of Institute "Jozef Stefan". And lastly we present some examples that use this method.
Keywords: atomska spektroskopija; biological tissues; biološka tkiva; metoda PIXE; PIXE emissions; spectroscopy